Superferromagnetic Nanoparticles Enable Order‐of‐Magnitude Resolution & Sensitivity Gain in Magnetic Particle Imaging. Issue 11 (12th September 2021) - Tay, Zhi Wei; Savliwala, Shehaab; Hensley, Daniel W.; Fung, K.L. Barry; Colson, Caylin; Fellows, Benjamin D.; Zhou, Xinyi; Huynh, Quincy; Lu, Yao; Zheng, Bo; Chandrasekharan, Prashant; Rivera‐Jimenez, Sindia M.; et al.
Abstract: Magnetic nanoparticles have many advantages in medicine such as their use in non‐invasive imaging as a Magnetic Particle Imaging (MPI) tracer or Magnetic Resonance Imaging contrast agent, the ability to be externally shifted or actuated and externally excited to generate heat or release drugs for therapy. Existing nanoparticles have a gentle sigmoidal magnetization response that limits resolution and sensitivity. Here it is shown that superferromagnetic iron oxide nanoparticle chains (SFMIOs) achieve an ideal step‐like magnetization response to improve both image resolution & SNR by more than tenfold over conventional MPI. The underlying mechanism relies on dynamic magnetization with square‐like hysteresis loops in response to 20 kHz, 15 kAm −1 MPI excitation, with nanoparticles assembling into a chain under an applied magnetic field. Experimental data shows a "1D avalanche" dipole reversal of every nanoparticle in the chain when the applied field overcomes the dynamic coercive threshold of dipole‐dipole fields from adjacent nanoparticles in the chain. Intense inductive signal is produced from this event resulting in a sharp signal peak. Novel MPI imaging strategies are demonstrated to harness this behavior towards order‐of‐magnitude medical image improvements. SFMIOs can provide a breakthrough in noninvasive imaging of cancer, pulmonary embolism, gastrointestinal bleeds, stroke, and inflammation imaging. Abstract : Magnetic particle imaging (MPI) is a new imaging method different from Magnetic Resonance Imaging that enables tracer‐like imaging of magnetic nanoparticles. This work demonstrates how superferromagnetism in a linear chain of iron oxide nanoparticles (SFMIOs) can be harnessed to improve MPI image spatial resolution and sensitivity tenfold. SFMIO potentially enables more sensitive and accurate cancer, vascular, and stem cell imaging.